Endovascular management of acute postprocedural flow diverting stent thrombosis. (17th September 2019) - Townsend, Robert Kyle; Wolfe, Stacey Q; Anadani, Mohammad; Spiotta, Alejandro; De Leacy, Reade; Mocco, J; Garner, Rebecca M; Albuquerque, Felipe C; Ducruet, Andrew F; Kan, Peter; Fargen, Kyle M
Abstract : Introduction: Postprocedural thrombosis is a rare complication after flow diverting stent (FD) implantation for aneurysm treatment with few reported cases in the literature. Management strategies and outcomes associated with this complication have not been reported. Methods: A multicenter retrospective series of cases of acute postprocedural FD thrombosis were compiled and prevalence was calculated based on procedural volumes over a 7 year period. Acute postprocedural FD thrombosis was defined as the development of neurologic deficit with angiographic imaging demonstrating acute thrombus within the index FD stent at least 2 hours following completion of the implantation procedure. Results: A total of 10 cases of postprocedural thrombosis were identified at five participating centers among a total of 768 patients treated (prevalence 1.3%). Thrombosis occurred a median of 5.5 days after implantation (range 0–83 days). 9/10 patients underwent emergent angiography with intent to perform endovascular reperfusion. A variety of different endovascular treatments were used, including aspiration thrombectomy, retrievable stent thrombectomy, balloon angioplasty, and intra-arterial thrombolytic infusion, without any procedural complications. There were no instances of FD migration, stent kinking, or aneurysm rupture. 90% of patients achieved Thrombolysis in Cerebral Infarction 2B or greater revascularization. Favorable clinical outcomes (modified Rankin Scale score of 0–2) at 3 months were achieved in 88% of patients. Conclusion: Acute postprocedural thrombosis of an FD is a rare complication that occurs in approximately 1–2% of patients after aneurysm treatment. Patients presenting with acute postprocedural FD thrombosis should be aggressively managed using large vessel occlusion thrombectomy techniques, as good angiographic and clinical outcomes are possible.